PENGENDALIAN MANAJEMEN: ASPEK KEPERILAKUAN PADA PERENCANAAN LABA DAN PENGANGGARAN - -, Rispantyo (Universitas Slamet Riyadi, 2010)
Abstract Accountancy expands speed. At last decade peeped out of related with accountancy is behavior aspect from all decision taker. This area is recognized with behavior accountancy, what is one of the areas is operation of management. Compilation budget is operational process plan in the form of quantitative, usually in the form of monetary unit, for the range of time of is certain. Budget have the character of is technical, but most human being element share. Budget has direct impact to human being. Behavior aspect which is related to budget refers to human being behavior in concerned at process compilation budget. Behavior aspect which must be gave attention to phase stipulating target is all planning aspect that covering participation, according to target, and commitment. Behavior aspect which must be gave attention to implementation phase cover communications, cooperation, and coordination. Behavior aspect which must be gave attention to operation phase and performance evaluation policy, attitude, management action in performance evaluation and follow-up to the deviation that happened. Keywords: operation of management, profit planning, budget